1988
DOI: 10.1111/j.1365-246x.1988.tb00464.x
|View full text |Cite
|
Sign up to set email alerts
|

The 1984 Round Valley, California Earthquake Sequence

Abstract: The 1984 November 23 ML 5.8 Round Valley earthquake is one in the.series of moderate earthquakes to have occurred in the Bishop-Mammoth Lakes, California area since 1978. This event and its aftershock sequence are particularly well recorded in that they occurred within a dense, local high frequency seismic network, and strong motion accelerograms, and regional and teleseismic digital seismograms are available for the main shock. We have derived the fault plane solution from the local and regional first motion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…Amplitudes were measured o simulated WWSSN short-period records using Nuttli's practice of taking the 3rd peak for both upswings and downswings and averaging the two amplitudes. This worked well for explosions at NTS, but PRIESTLEY and PATTON (1997) found that adopting the same Q 0 values obtained by Nuttli and Patton led to overestimation of m b (Lg) for earthquakes located near the test site. In Vol.…”
Section: Western United States (Wus) Data Setsupporting
confidence: 64%
“…Amplitudes were measured o simulated WWSSN short-period records using Nuttli's practice of taking the 3rd peak for both upswings and downswings and averaging the two amplitudes. This worked well for explosions at NTS, but PRIESTLEY and PATTON (1997) found that adopting the same Q 0 values obtained by Nuttli and Patton led to overestimation of m b (Lg) for earthquakes located near the test site. In Vol.…”
Section: Western United States (Wus) Data Setsupporting
confidence: 64%
“…Following this line of reasoning, it will be shown that the CLVD decomposition is to be preferred in the absence of compelling source complexity or other situations which would lead to major and minor couples. Conversely, it can be argued that reporting the source in terms of major + minor double couples as done recently by Priestley, Smith & Cockerham (1988) is as reasonable as reporting a double couple + CLVD, as is more common, in the absence of the kind of mathematical arguments presented here.…”
Section: Introductionmentioning
confidence: 77%
“…The additional high-frequency energy causing the spectrum to drop off with a slope less than co-2 past the comer frequency can arise due to fault roughness (Gusev 1983). Such effects have been observed for earthquakes over a wide magnitude range Brune et al 1986;Smith et al 1988). The lack of this roughness energy in the spectrum of the Edgecumbe earthquake indicates a relatively uniform rupture process.…”
Section: Source Parameters Of the Main Shockmentioning
confidence: 84%
“…This presumably represented the upper limit for the surface which slipped during the main shock. In several cases where dense seismograph networks were in place at the time of a main shock, allowing accurate aftershock locations immediately following a main event, it has been observed that the aftershock zone grew in size by 10-20 % in the first few hours (e.g., Smith & Priestley 1988;Priestley et al 1988). This is to be expected since aftershocks should be most frequent at the boundaries of the slip zone where the main shock has increased the stress.…”
Section: Source Parameters Of the Main Shockmentioning
confidence: 85%
See 1 more Smart Citation